Improvement in the nutraceutical properties of fenugreek (Trigonella foenum-graecum L.) - Saikat Basu; Buncha Ooraikul; Tapan Basu; Anchalee Srichamroen; Surya Acharya (Songklanakarin Journal of Science and Technology (SJST), 2006)
Fenugreek (Trigonella foenum-graecum L.) leaves and seeds have been used extensively for medicinal purposes. Fenugreek seed is known to exhibit anti-diabetic and anti-nociceptive properties and effects such as hypocholesterolaemic, anti-cancer and thyroxine-induced hyperglycaemia. Our research objectives have been to identify the chemical constituent(s) responsible for the health effects in human and to develop a strategy for improving these constituents in fenugreek plants. We have observed considerable variability among fenugreek genotypes. They differ in morphology, growth habit, biomass and seed production capability. Chemical constituents of the seed, e.g. saponins, fibre, protein, amino acids and fatty acid contents also differ markedly. This variability is most often overlooked or underestimated in clinical trials. Our research suggests that the genetic variability and the genotype by environmental interaction will play a significant role when the crop is used by the nutraceutical industry in Canada where high quality seed production is at present difficult. Our multi-disciplinary approach aims at understanding the processes involved in the genetic improvement of fenugreek and use the new knowledge to improve the crop. We have developed a fenugreek cultivar "Tristar" for western Canada that can produce very high quality forage and will now concentrate on producing cultivars having improved nutraceutical value. Our research results indicate that the variability for important traits in fenugreek have a genetic base, making selection for improved levels of these traits possible.